Integrasi antara Ekonomi Syariah dan Hukum Ekonomi Syariah dalam Perspektif Disiplin Keilmuan Ekonomi - Sumarta, Sumarta (Tasyri' : Jurnal Muamalah dan Ekonomi Syariah, 2023)
The integration between Islamic Economics and Islamic Economic Law has become an increasingly intriguing subject in modern economic studies. This paper discusses the perspective of economic disciplines on this integration, highlighting key aspects related to the close relationship between Islamic economic principles and Sharia law. By analyzing economic theories and Islamic legal principles, this integration offers a holistic approach to developing an economic model aligned with Islamic values. The findings of this research reveal that a holistic approach encompassing economic, legal, social, and cultural aspects is necessary to integrate Islamic Economics and Islamic Economic Law, in order to understand the complex relationships in the ever-evolving global economic context. The challenges of interpreting and harmonizing economic and Islamic legal principles require further efforts to strengthen a consistent framework. Supportive regulations and policies are crucial to facilitating this integration, with collaboration between policymakers, economists, and legal experts. Enhancing education and awareness about Islamic economic principles and Islamic economic law among the general public, practitioners, and policymakers is a critical step. Moreover, empowering the local economy through this integration can strengthen local economies and support the growth of small and medium enterprises, thereby achieving inclusive economic development. Keywords: Sharia Economics Integration, Sharia Economic Law, Economic Disciplinary Perspective, Islamic Economic Model, Islamic Values.